Multichannel unidirectional perfect absorbers on sandwich structures with truncated symmetric photonic crystals - Guang Lu; Liyong Cui; Bin Liu; Jin Li; Feng Sun; Shan Zhang; Fen Liu; Yanhui Li; Tianlin Yang; Guiqiang Du (AIP Advances, 2018)
We experimentally studied unidirectional perfect absorbers with asymmetric sandwich structures composed of two thick metallic films with different thicknesses and a truncated symmetric photonic crystal (PC). Single-channel and multichannel near-perfect absorbers were obtained by adjusting period number of the PC. According to electromagnetic field intensity distributions at absorption wavelengths, the physical mechanism of near-perfect absorption derived from the coupling effect between optical Tamm state and Fabry-Pérot resonance. The unidirectional absorption phenomena were attributed to weak electric field distributions at absorption wavelengths for opposing directions of light incidence. The experimental values showed good agreement with theoretical results.